2016
DOI: 10.1093/europace/euw176
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of battery longevity in implantable cardioverter-defibrillators for cardiac resynchronization therapy: the hospital and healthcare system perspectives

Abstract: AimsPatients receiving cardiac resynchronization therapy defibrillators (CRT-Ds) are likely to undergo one or more device replacements, mainly for battery depletion. We assessed the economic impact of battery depletion on the overall cost of CRT-D treatment from the perspectives of the healthcare system and the hospital. We also compared devices of different generations and from different manufacturers in terms of therapy cost.Methods and resultsWe analysed data on 1792 CRT-Ds implanted in 1399 patients in 9 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Device replacement not only increases the risk of complications but also the total cost of therapy given the additional procedures required and extra costs associated with managing replacement-related complications. 21 The longevity of CRT-D batteries has been found to be shorter than that of single- and dual-chamber defibrillator batteries 23 and, historically, ERI has been the most frequent cause of device replacement reported in prior studies. 2 , 24 , 25 To our knowledge, our study is the first to report patient deaths as a more frequent cause of CRT-D OOS (mean time to death: 2.3 ± 2.1 years) rather than ERI (mean time to ERI: 7.8 ± 1.5 years), likely due to our focus on 2.1-Ah battery CRT-D systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Device replacement not only increases the risk of complications but also the total cost of therapy given the additional procedures required and extra costs associated with managing replacement-related complications. 21 The longevity of CRT-D batteries has been found to be shorter than that of single- and dual-chamber defibrillator batteries 23 and, historically, ERI has been the most frequent cause of device replacement reported in prior studies. 2 , 24 , 25 To our knowledge, our study is the first to report patient deaths as a more frequent cause of CRT-D OOS (mean time to death: 2.3 ± 2.1 years) rather than ERI (mean time to ERI: 7.8 ± 1.5 years), likely due to our focus on 2.1-Ah battery CRT-D systems.…”
Section: Discussionmentioning
confidence: 99%
“…CRT-D replacement due to battery depletion is a significant cost-driver for payors 21 , 26 and a significant complication-driver for patients. 9 , 18 Landolina et al found the need for device replacements at six years was reduced from 83% to 68% with the use of devices with improved battery longevity from the most recent generation.…”
Section: Discussionmentioning
confidence: 99%
“…Even among those 14 patients with ample use of ICD electrical therapy or an electrical storm, only 1 was apparently affected and presented premature battery depletion. Although reports of longevity have indicated a progressive increase of the life span of ICD devices over the years, from a mean of 19 months in 1980 to 48 months in 2009 to 65 months in 2015, there is still room for improvement, as this is quite an expensive therapy and patient and physician expectations run high for a more satisfactory performance of these devices, a crucial determinant of cost‐efficacy of ICD therapy . Reducing the frequency of generator replacements would also reduce the frequency of important complications, such as device infection, and their consequent costs .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, for CRT to be effective, constant left ventricular or biventricular pacing is a prerequisite to ensure left ventricular resynchronization . According to a recent study in a large cohort of 1399 patients treated with CRT‐D, device replacement for battery depletion proved to be a significant cost driver, whereby improved longevity observed with newer‐generation devices reduced the therapy cost . Furthermore, differences were also observed among CRT‐D systems from different manufacturers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation